2021
DOI: 10.1016/j.crfs.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 on surfaces in food retailers in Ontario

Abstract: The COVID-19 pandemic has generated increased interest in potential transmission routes. In food retail settings, transmission from infected customers and workers and customers through surfaces has been deemed plausible. However, limited information exists on the presence and survival of SARS-CoV-2 on surfaces, particularly outside laboratory settings. Therefore, the purpose of this project was to assess the presence of the virus at commonly found surfaces at food retail stores and the potential role that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
(32 reference statements)
0
11
2
Order By: Relevance
“…Instead, COVID-19 spreads primarily via aerosol droplets when infected people cough, sneeze, or speak ( Siordia, 2020 ; Hatmi, 2021 ; Lewis, 2021 ;). If preventive measures and sanitizing routines are maintained, the risk of COVID-19 infection from contact with a contaminated surface is less than 5 in 10,000, which is lower than the surface transmission risk for the common flu ( Lewis, 2021 ; Singh et al, 2021 ). Therefore, this science-based evidence undermines the argument to use SUPs as a health measure to prevent COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, COVID-19 spreads primarily via aerosol droplets when infected people cough, sneeze, or speak ( Siordia, 2020 ; Hatmi, 2021 ; Lewis, 2021 ;). If preventive measures and sanitizing routines are maintained, the risk of COVID-19 infection from contact with a contaminated surface is less than 5 in 10,000, which is lower than the surface transmission risk for the common flu ( Lewis, 2021 ; Singh et al, 2021 ). Therefore, this science-based evidence undermines the argument to use SUPs as a health measure to prevent COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 97%
“…Further, laboratory studies suggest prolonged SARS-CoV-2 infectivity (days to weeks) ( Riddell et al, 2020 ) on surfaces ( Pastorino et al, 2020 ; van Doremalen et al, 2020 ) and low temperatures and humidity (common in cold-chain conditions) were associated with virus stability (months or longer) ( Aboubakr et al, 2021 ). SARS-CoV-2 viral RNA has been detected on surfaces in playgrounds, retail stores ( Harvey et al, 2021 ; Singh et al, 2021 ), and healthcare settings ( Jiang et al, 2020 ; Ong et al, 2020 ). However, the relationship between detectable viral RNA and infectious virus is tenuous (estimated 4:1 ratio viral RNA copies to infectious virus) ( Sender et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, any secondary viral contamination of food stuffs is minimized by following hygiene and sanitation rules, and safety procedures from the initial supply of the raw material (i.e., harvesting for vegetables, or slaughter for fish/meat products), to processing, packaging, and distribution, recommended also by WHO and EFSA [ 27 , 29 , 78 ]. A recent study in a retail store suggested preventive measures and sanitizing routines were necessary methods to minimize the exposure risk from contaminated high-touch surfaces [ 79 , 80 ]. Literature reported that the greatest risk for the food industry is transmission among workers, further highlighting the need for innovative and effective disinfection strategies that must be implemented in the workplace to avoid SARS-CoV-2 transmission [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%